Types and abundance of periphyton on glass substrate in parit belanda river, rumbai pesisir district, pekanbaru city, Riau - Rahmi Hidayana Hasibuan; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Periphyton is a group of microorganisms that grow in some natural subsrates such as rock, wood, plants and aquatic animals. A research aims to understand the type and abundance of periphyton at smooth surface glass and rough surface glass in the Parit Belanda River has been carried out in March-April 2016. There are three station namely station 1 up stream, station 2 in the middle of stream, and station 3 at down stream. Sampling once/week for a 4 weeks period. The periphyton samples were brushed from the surface of glass substrate (8 cm x 3 cm). Type of periphyton was identified based on Bigg and Killroy (2000), Yunfang (1995) and Prescot (1974). Result shown that there are 36 types of phytoperiphyton are belonged to 4 classes, namely Bacillariophyceae (17 species), Chlorophyceae (10 species), Cyanophyceae (8 species) Rhodophyceae (1 spesies), whereas zooperiphyton are belonged to 5 classes, namely Monogononta (9 spesies), Euglenophyceae (3 spesies), Crustacea (1 spesies), Adenophprea (1 spesies) and Insecta (1 species). The abundance of phytoperiphyton attached in the smooth surfaced glass was 18,790-25,230 cells/cm2 and the zooperiphyton was 1,400-2,540 organisms/cm2. While the rough surfaced glass, it was 20,780-30,450 cell/cm2 and the zooperiphyton was 1,280-1,470 organisms/cm2. Based on the composition of periphyton, it can be concluded that the Parit Belanda River can be categorized as eutrophic.Keywords: Parit Belanda River, Periphyton, Glass Substrates